Enhancing Community Economy through Jollong Gardens: A Local Heritage and Ecotourism Strategy - Anisa Nur Hidayah; Kusumantoro; Moch Faizal Rachmadi (Soshum: Jurnal Sosial dan Humaniora, 2024)
Agrotourism in Indonesia plays a crucial role in enhancing community economic inclusiveness by providing employment and empowerment opportunities. Jollong Gardens Agrotourism, a notable destination in Pati Regency, Central Java, serves as the focal point of this study. The research aims to: 1) Assess tourism management capacity in Pati Regency, 2) Analyze the sustainable integration of the tourism sector, and 3) Develop a strategy for Jollong Gardens Agrotourism based on local heritage and ecotourism to boost community economic inclusiveness. Using a mixed-methods approach, the study combines descriptive qualitative analysis with the Analytic Network Process (ANP) for quantitative analysis, utilizing both primary and secondary data. The findings indicate a need to improve human resource quality to optimize tourism contributions, highlight the importance of stakeholder synergy with a high contribution value of 0.16584, and prioritize enhancing human resource quality and competency for Jollong Gardens Agrotourism with a value of 0.36710.